Caribou in British Columbia: A 1996 status report - Heard, Douglas C.; Vagt, Kathryn L. (Rangifer, 1998)
Caribou (Rangifer tarandus) in British Columbia are classified into mountain, northern and boreal ecotypes based on behavioural and ecological characteristics. We recognized 12 mountain caribou herds, 27 northern caribou herds, and an area occupied by low density boreal caribou dispersed in the boreal forests of the northeast portion of the province. Abundance estimates were usually based on attempts at total counts made from the air. Trends were based on repeated population estimates or the difference between recruitment and mortality rates for each herd. In 1996 there were approximately 18 000 caribou in British Columbia; 2300 mountain and 15 600 northern and boreal. These estimates suggest a slight increase in the numbers of both ecotypes over the last 18 years. Fifteen percent of the herds were reportedly increasing, 10% were decreasing, 31% were stable, but for 44% of the herds the trend was unknown. Historically caribou were found throughout 8 of the 14 biogeoclimatic zones in B.C. Caribou are now rarely found in the Sub-Boreal Spruce zone, likely due to increased predation from wolves that increased in response to increasing moose numbers. Ranges of several herds in the Engelmann Spruce — Subalpine Fir and Alpine Tundra zones of south-eastern British Columbia are also reduced relative to historic conditions, probably because of habitat loss, habitat fragmentation, predation and hunting. Forest harvesting represents the greatest threat to caribou habitat and current research focuses on the mitigation of forest harvesting impacts.